Studi Islam dalam Pendekatan Hukum; Implementasi, Tantangan dan Peran Dakwah (Sebuah Analisis Multidisipliner di Negara Pluralistik) - Asrizal; Delmus Puneri Salim; Suharmon (TEKNO AULAMA: Jurnal Teknologi Pendidikan Islam, 2025)
This study is multidisciplinary, combining history, culture, and Islamic thought to achieve a holistic understanding. Islamic law is analyzed as part of the social and national legal system using a legal-positivist, pluralistic, and integrative-nationalistic approach, which unites Islamic values with national law based on Pancasila and Bhinneka Tunggal Ika. General legal theories such as Natural Law, Legal Positivism, Sociological Law, Progressive Law, and Critical Law are used as lenses of analysis. Data is divided into normative (written) and empirical (living in society), analyzed doctrinally, sociologically, or in combination, with implementation through legislation and socio-legal means. Challenges in pluralistic countries include legal pluralism, substantive justice, value conflicts, identity politics, and biased law enforcement. Da'wah plays a role as social engineering to build harmony, a culture of compliance, and ensure that the law protects maqāṣid al-syarī‘ah and maintains social solidarity